What do we tell patients about elective total hip replacement in the UK?: an analysis of patient literature - Drummond, Avril E.R.; Edwards, Claire; Coole, Carol; Brewin, Catherine (BioMed Central, 2013)
Background: Although hip information literature is given to people following total hip replacement (THR) almost routinely, little evaluation has been conducted on it to date. Our aim was therefore to analyse and evaluate the literature provided to patients by occupational therapists concerning elective hip surgery in the UK.